ANALISIS PENGARUH KUALITAS PELAYANAN DAN NILAI PELANGGANTERHADAP KEPUASAN PELANGGAN DAN WORD OF MOUTH PADA PDAMTIRTA INDRAGIRI TEMBILAHAN - Yuniarti, Nur; Hendriani, Susi (Jurnal Tepak Manajemen Bisnis, 2016)
This studyaims to determinethe influence ofService Quality andCustomer ValueonCustomerSatisfactionandWordofmouthonPDAMTirtaIndragiriTembilahan. Populationis also thesample which ofPDAM TirtaIndragiriTembilahanas many as200customers. The samplingmethodused isprobability samplingtechnique. StructuralEquation Modeling(SEM) was usedasthe data analysisandprocessingwith Partial Least Square (PLS) 1 software.These resultsindicatethatcustomervaluehas asignificantpositiveeffecton satisfactionand word ofmouth.Servicequalityhassignificant positive effect onsatisfaction, butservice qualityhasapositiveeffectbutnot significant to theword ofthe mouth. In adition besides to thatthesatisfaction ofcausingamplifyingeffecton the quality ofservicesand customer value.The studyrecommends that PDAM Tirta Indragiri Tembilahan to increase positive word of mouth byimproving customer satisfaction, by providing services and customer value that meetscustomer expectations. The improvement of service quality is detected to the quality ofimprovement physical and can be directed to strengther customer value.